Microbes, intestinal inflammation and probiotics. (February 2012) - Khan, Mohammad W; Kale, Amod A; Bere, Praveen; Vajjala, Sriharsha; Gounaris, Elias; Pakanati, Krishna Chaitanya
Inflammatory bowel disease (IBD) is known for causing disturbed homeostatic balance among the intestinal immune compartment, epithelium and microbiota. Owing to the emergence of IBD as a major cause of morbidity and mortality, great efforts have been put into understanding the sequence of intestinal inflammatory events. Intestinal macrophages and dendritic cells act in a synergistic fashion with intestinal epithelial cells and microbiota to initiate the triad that governs the intestinal immune responses (whether inflammatory or regulatory). In this review, we will discuss the interplay of intestinal epithelial cells, bacteria and the innate immune component. Moreover, whether or not genetic intervention of probiotic bacteria is a valid approach for attenuating/mitigating exaggerated inflammation and IBD will also be discussed.